The Comparison of Peter Parker’s Language Styles and Style-Shifting Occurrences in Jon Watts’ Spider- Man: Homecoming (2017) and Spider-Man: No Way Home (2021) Movies - Zulhelmi, Mutiara Luthfiyanti; Oktoviandry, Rifki (English Language and Literature, 2024)
This study analyzes the language style and style-shifting in Peter Parker's conversations in two movies directed by Jon Watts: Spider-Man: Homecoming (2017) and Spider-Man: No Way Home (2021). A descriptive-qualitative method was used to analyze the data. This study found that the casual language style is the most dominant in both movies. This is related to Joos' (1967) "Five Clocks of Language" with the casual type which is a relaxed, natural, and unrestricted manner language style used in everyday life. Spider-Man: Homecoming (2017) shows that the most prominent style-shifting is maintenance, indicating Peter Parker's tendency to maintain the language style. Meanwhile, in Spider-Man: No Way Home (2021) although casual style remains dominant,  Peter tended to shift his style with upward convergence, indicating that Peter Parker often adapts his interaction to be more formal. This style-shifting is related to Giles’ (1973) “Communication Accommodation Theory” with the upward convergence strategy used to adjust one’s communication style to be aligned with the interlocutor by being more formal and using a more prestigious language. While maintenance strategy occurs when a speaker chooses not to alter their communication style and use their own style consistently throughout the interaction. This difference reflects the development of Peter Parker's character between the two movies, with a more consistent style in Spider-Man: Homecoming (2017), compared to a more dynamic style adaptation in Spider-Man: No Way Home (2021).